Kariera zawodowa kobiet we współczesnych organizacjach - Christoph , Monika; Krause , Ewa (Studia Edukacyjne, 2019)
The article presents the specificity of women’s professional careers and their situation and social roles in the context of dynamic changes in the labor market: evident intellectualization and digitization of working environments, significantly changing career concepts as well as ways to achieve it. This is particularly important in relation to the career paths of women, mainly due to the need to reconcil work with family responsibilities. Therefore, it becomes important to highlight practical solutions for organizations that aim to create programs to support women in their aspirations and career ambitions, to make work time more flexible and to promote gender diversity in the field of organizational culture.